1968
DOI: 10.1007/bf02540172
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chlorinated pesticides from crude vegetable oils by simulated commercial processing procedures

Abstract: Crude soybean and cottonseed oil were processed using simulated commercial processing procedures to determine if oil processing would remove chlorinated pesticide contaminants of either natural or spiked origin. Two crude oil lots were spiked with endrin, DDT, DDE, aldrin, dieldrin, heptaehlor and heptaehlor epoxide before processing. Representative samples of crude oil and products following each processing step were analyzed for pesticide contamination. Results indicated that alkali-refining or subsequent bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The same observation was reported by Mounts et al [3] a few months later through their radiochemical experiments with soybean oil ( 14 C-endrin and 14 C-benzo(a)pyrene). The observation on the failure of the bleaching step in the removal of endrin confirmed the hypothesis suggested by Smith et al [2].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The same observation was reported by Mounts et al [3] a few months later through their radiochemical experiments with soybean oil ( 14 C-endrin and 14 C-benzo(a)pyrene). The observation on the failure of the bleaching step in the removal of endrin confirmed the hypothesis suggested by Smith et al [2].…”
Section: Introductionsupporting
confidence: 89%
“…Over the past few decades, there were relatively few reports regarding studies on the fate of pesticide residues during vegetable oil processing. Smith et al [2] reported that chemical refining was effective in removing chlorinated pesticides (endrin, DDT, DDE, aldrin, dieldrin, heptachlor and heptachlor epoxide) in simulated commercial refining process experiments with crude soybean oil and cottonseed oil. They postulated that the removal of these pesticides was achieved by volatilization during the deodorizing step.…”
Section: Introductionmentioning
confidence: 99%
“…studies on the behavior and reduction of organochlorine compounds at different refining steps (i.e. degumming, alkali refining and bleaching with activated earth) have in some cases indicated similar effects [17,18,35]. However, these authors concluded that the studied processing steps had no significant effect on the concentration of contaminants.…”
Section: Effect Of Alkali Refining and Bleachingmentioning
confidence: 88%
“…The byproduct of the reaction are hydrogen chloride and low molecular weight hydrocarbon [53]. Endrin and some other organochlorine pesticides have been successfully degraded by hydrogenation, followed by deodorization [40]. Furthermore, the research conducted by Addisson and Ackman [7] removed polychlorinated biphenyl, DDT and dieldrin from margarine by dehydrogenation followed by deodorization.…”
Section: Methods For Removal Of Organochlorine Pesticides From the Environmentmentioning
confidence: 99%